2015
DOI: 10.1371/journal.pone.0127207
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Breakdown in Cichlid Fish

Abstract: Studies from a wide diversity of taxa have shown a negative relationship between genetic compatibility and the divergence time of hybridizing genomes. Theory predicts the main breakdown of fitness to happen after the F1 hybrid generation, when heterosis subsides and recessive allelic (Dobzhansky-Muller) incompatibilities are increasingly unmasked. We measured the fitness of F2 hybrids of African haplochromine cichlid fish bred from species pairs spanning several thousand to several million years divergence tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
58
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 47 publications
4
58
0
Order By: Relevance
“…Since T. cristatus – T. marmoratus hybrids are largely sterile and introgression is near‐absent, hybridization between these two species appears to be an evolutionary dead‐end (Arntzen et al, , ). This supports the theory of hybrid breakdown in the F 2 , similar to the study of Stelkens et al () on cichlid fish hybrids. At the other side of the coin, heterosis appears to be absent when there is gene flow, as in the hybrid population of T. macedonicus and T. ivanbureschi (Arntzen et al, ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Since T. cristatus – T. marmoratus hybrids are largely sterile and introgression is near‐absent, hybridization between these two species appears to be an evolutionary dead‐end (Arntzen et al, , ). This supports the theory of hybrid breakdown in the F 2 , similar to the study of Stelkens et al () on cichlid fish hybrids. At the other side of the coin, heterosis appears to be absent when there is gene flow, as in the hybrid population of T. macedonicus and T. ivanbureschi (Arntzen et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…Studies from a wide range of taxa have shown a negative relationship between genetic compatibility and the divergence time of hybridizing genomes (Stelkens et al, ), since selection acts against hybrid individuals, probably due to disadvantageous combinations of co‐adapted gene complexes derived from either parental species, the so‐called Dobzhansky–Muller model of hybrid incompatibility (e.g., Parsons, Olson, & Braun, ; Wu & Ting, ). Theory predicts the main breakdown of fitness to happen after the F 1 hybrid generation, when heterosis subsides and recessive allelic incompatibilities are increasingly unmasked and cause hybrid sterility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incredibly recent timeframe during which the several hundred species within Lake Malawi have diverged has provided comparatively little time for intrinsic reproductive barriers to arise and reduce hybrid viability154950. Therefore, hybridization and transgression in Lake Malawi cichlids could readily occur between two species with highly divergent trophic morphologies because hybridization between Lake Malawi cichlids is very common1114.…”
Section: Discussionmentioning
confidence: 99%
“…Third, disruption of co‐adapted nDNA gene complexes can cause hybrid breakdown, particularly following recombination in second‐generation hybrids and beyond (e.g., Rogers and Bernatchez ; Stelkins et al. ). The detection of inferred F 2 × pure backcrosses in our study indicates that at least some second‐generation hybrids were fertile and at least some third‐generation hybrids were viable.…”
Section: Discussionmentioning
confidence: 99%